FAKTOR - FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Erra Mariski, Liana Susanto (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to obtain empirical evidence about the effects of accruals, operating cash flows, leverage, and firm size on earnings persistence in manufacturing industries listed in Indonesian Stock Exchange during the periode of 2015-2017. This research used 61 samples from selected manufacturing companies with purposive sampling method. The data in this research were calculated with Microsoft Office 365 software and processed with Eviews 9.0. The results obtained in this research show that accruals, operating cash flows, and firm size have a significant effect on earnings persistence, while leverage has insignificant effect on earnings persistence.